2014
DOI: 10.1103/physrevlett.113.205501
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of a Multiphysics Cloak: Manipulating Heat Flux and Electric Current Simultaneously

Abstract: In past years, triggered by their successful realizations in electromagnetics, invisible cloaks have experienced rapid development and have been widely pursued in many different fields, though so far only for a single physical system. In this letter we made an unprecedented experimental attempt to show a multidisciplinary framework designed on the basis of two different physical equations. The proposed structure has the exceptional capability to simultaneously control two different physical phenomena according… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
152
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(156 citation statements)
references
References 42 publications
(25 reference statements)
1
152
2
1
Order By: Relevance
“…17,18 The efficiency of the bilayer approach proposed by the first group was quickly verified and applied to other Laplace equations governing the evolutions of different physical phenomena. [25][26][27][28][29][30][31] In practice, a magnetic cloak that is able to perform under alternating currents will be more meaningful, as one usually relies on EM induction to uncover hidden metallic or magnetic objects. The same group extended their original two-dimensional bilayer design to A.C. fields and indicated a technical possibility within a frequency range of several hundred Hertz.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The efficiency of the bilayer approach proposed by the first group was quickly verified and applied to other Laplace equations governing the evolutions of different physical phenomena. [25][26][27][28][29][30][31] In practice, a magnetic cloak that is able to perform under alternating currents will be more meaningful, as one usually relies on EM induction to uncover hidden metallic or magnetic objects. The same group extended their original two-dimensional bilayer design to A.C. fields and indicated a technical possibility within a frequency range of several hundred Hertz.…”
Section: Introductionmentioning
confidence: 99%
“…This multiphysical invisible sensor has three features that distinguish it from conventional DC and thermal metamaterial devices, especially different from the bifunctional cloak for an air cavity. [ 40 ] First, we allow the sensor to "see through and behind" the cloaked region in multiphysical fi elds. As a result, the sensor is invisible and receives proportional incoming signals at the same time, and it is able to "open its eyes" behind the cloak to receive information from the outside multiphysical When a sensor is used to probe a physical fi eld, it intrinsically disturbs surrounding environment, introduces perturbation and unwanted noise in the measurement.…”
mentioning
confidence: 99%
“…Later, the fi rst experiment was carried out to simultaneously cloak an air cavity in the electric and thermal fi elds. [ 40 ] This sample was fabricated through a sophisticated man-made metamaterial structure with many holes drilled in a silicon plate that were, then, fi lled with poly(dimethylsiloxane) (PDMS). In our work, we found that natural materials with simple structure can also simultaneously manipulate multiphysical fi elds.…”
mentioning
confidence: 99%
“…This process allows us to design switchable thermal cloaks and then macroscopic thermal diodes. The former serve as an extension of the extensively investigated cloaks without switches [16][17][18][19][20][21][22][23]31]; the latter are actually a useful application of the former in this work. We proceed as follows.…”
Section: Temperature-dependent Transformation Thermoticsmentioning
confidence: 99%
“…The cloaking originates from the fact that the thermal conduction equation remains form-invariant under coordinate transformation. So far, the theoretical proposal of steady-state thermal cloaking [16] and its extensions (say, bifunctional cloaking of heat and electricity [17] or nonsteady-state thermal cloaking [18]) have been experimentally verified and developed [19][20][21][22][23]. The theoretical treatment based on coordinate transformation [16][17][18][24][25][26][27][28], which is called transformation thermotics (or transformation thermodynamics), has a potential to become a fundamental theoretical method for macroscopically manipulating heat flow at will.…”
mentioning
confidence: 99%